2009 IEEE Intrumentation and Measurement Technology Conference 2009
DOI: 10.1109/imtc.2009.5168663
|View full text |Cite
|
Sign up to set email alerts
|

Design of a tropical rain - Disaster alarm system: A new approach based on wireless sensor networks and acoustic rain rate measurements

Abstract: This paper discusses the design of a broadband wireless network infrastructure which itself is a rain measurement platform for applications such as disaster alarm and sudden hazard decision management systems. A sensor testbed is setup which consists of a hybrid broadband wireless network in conjunction with real-time acoustic rain rate point sensors and complementary rain gauges. The testbed simulates the commercial deployment of a line-of-sight wireless backbone (implemented via a 26 GHz line of sight link) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 5 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…Experimental values, in general, have a large deviation from those given by the theoretical and empirical models. Few other works present the RSSI measurements for wi-fi links such as Libatique et al (2009) showed for a 3 dB signal attenuation at 5 GHz for a transmitter-receiver distance of 0.4 km and a 12 mmÁhr -1 rainfall intensity, which yields a specific signal attenuation of 7.5 dBÁkm -1 . Karagianni et alʼs (2016) measurements for moderate rainfall events around 12 mmÁhr -1 showed a power loss around 12 dBm at 2.4 GHz; supposing that a maximum path loss of 1.6 km was used, this yields specific path attenuation from 7.5 (for the case of maximum wi-fi distance) to 15 dBÁkm -1 .…”
Section: Measurements Near This Frequency Bandmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental values, in general, have a large deviation from those given by the theoretical and empirical models. Few other works present the RSSI measurements for wi-fi links such as Libatique et al (2009) showed for a 3 dB signal attenuation at 5 GHz for a transmitter-receiver distance of 0.4 km and a 12 mmÁhr -1 rainfall intensity, which yields a specific signal attenuation of 7.5 dBÁkm -1 . Karagianni et alʼs (2016) measurements for moderate rainfall events around 12 mmÁhr -1 showed a power loss around 12 dBm at 2.4 GHz; supposing that a maximum path loss of 1.6 km was used, this yields specific path attenuation from 7.5 (for the case of maximum wi-fi distance) to 15 dBÁkm -1 .…”
Section: Measurements Near This Frequency Bandmentioning
confidence: 99%
“…Additionally, a measurement of rain attenuation for a link in the S-band was carried out. In a proposed disaster alarm system (Libatique et al, 2009), the 5 GHz link was deployed over 400 m and monitoring was performed during rainy and clear days. A nationwide experiment in the Philippines used a 5 GHz fixed wireless network as a rain alarm system for monitoring changes in the RSLs.…”
Section: Introductionmentioning
confidence: 99%
“…The great improvement in the fields of computer technology helps improve research and innovations. These improvements are greatly influenced by advanced researches communications engineering [1], [2], bio-medical engineering [3]. [4], [5] and robotics engineering [6] , [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in computer technology has played a very important role in simplifying systems analysis and design whether they are used in robotics, medical technology or pure communications systems design [1], [2] Throughout the years, convenience has been the aim of our country's technology. This is very evident and can be visibly seen in things like minimizing the usage of bigger components, transforming large machines into integrated circuits packed in smaller chips, and improving the speed of devices.…”
Section: Introductionmentioning
confidence: 99%